1983
DOI: 10.1111/j.1432-1033.1983.tb07357.x
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Phosphatases Involved in Cellular Regulation. 1. Classification and Substrate Specificities

Abstract: The protein phosphatase activities involved in regulating the major pathways of intermediary metabolism can be explained by only four enzymes which can be conveniently divided into two classes, type-1 and type-2. Type-I protein phosphatases dephosphorylate the 8-subunit of phosphorylase kinase and are potently inhibited by two thermostable proteins termed inhibitor-I and inhibitor-2, whereas type-2 protein phosphatases preferentially dephosphorylate the a-subunit of phosphorylase kinase and are insensitive to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
252
0
7

Year Published

1985
1985
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 489 publications
(272 citation statements)
references
References 63 publications
13
252
0
7
Order By: Relevance
“…Mn2+ (1.0 mM) also had no effect or inhibited protein phosphatase-1, except when inhibitor-1 was the substrate. As noted previously [30,31], the dephosphorylation of inhibitor-1 was almost completely dependent on Mn2+, half-maximal activation occurring at about 0.2 mM Mn2+.…”
Section: Influence Of Divalent Cations On the Activity Of Protein Phomentioning
confidence: 60%
See 2 more Smart Citations
“…Mn2+ (1.0 mM) also had no effect or inhibited protein phosphatase-1, except when inhibitor-1 was the substrate. As noted previously [30,31], the dephosphorylation of inhibitor-1 was almost completely dependent on Mn2+, half-maximal activation occurring at about 0.2 mM Mn2+.…”
Section: Influence Of Divalent Cations On the Activity Of Protein Phomentioning
confidence: 60%
“…6). The amino acid sequence immediately following sites-3 of glycogen synthase is extremely acidic (16 out of 31 residues) [39] and it has been suggested that acidic residues C-terminal to phosphorylation sites may act as negative specificity determinants for protein phosphatases [40]. It is possible that spermine interacts with this acidic region, thereby neutralising its inhibitory effects on the dephosphorylation of sites-3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ingebritsen and Cohen [3] have classified all protein phosphatases involved in the dephosphorylation of phosphoenzymes of intermediary metabolism. They arrived at the conclusion that these dephosphorylations are catalyzed by only four different protein phosphatases, termed phosphaiase 1, 2A, 2B and 2C.…”
Section: Introductionmentioning
confidence: 99%
“…
A recently described 6-phosphofructo-1-kinase phosphatase (PFK-phospatase [l]) shared several properties with protein phosphatase 2C [2,3], but exhibited differences with respect to molecular mass and substrate specificity. Chromatography on histone-Sepharose, gel filtration experiments on Sephacryl S-200 and Sephadex G-100 as well as sucrose density gradient centrifugation [4] show that both enzyme preparations behave identically under all experimental conditions used.
…”
mentioning
confidence: 99%